2003
DOI: 10.1002/zoo.10093
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive status of endemic felid species in Latin American zoos and implications for ex situ conservation

Abstract: Reproductive evaluations were conducted on 185 male cats representing eight endemic Latin American species that were maintained in 44 zoos and private facilities in 12 Latin American countries. Reproductive assessments (testicular measures, ejaculate quality, and blood testosterone/cortisol concentration) were used to establish normative values for large-and small-sized cats in Latin American collections. Data also were analyzed using multiple regression to study the impact of proven breeder status, diet, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 41 publications
1
42
1
11
Order By: Relevance
“…27 Reproductive Of the 185 male cats assessed, the level of successful captive breeding was low, with only 37 males (20%) classified as proven breeders (produced at least one offspring). 27 The majority of these proven breeders were jaguars, pumas, and ocelots.…”
Section: Imbalanced Diets and Fertility In Felids Latin American Catsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Reproductive Of the 185 male cats assessed, the level of successful captive breeding was low, with only 37 males (20%) classified as proven breeders (produced at least one offspring). 27 The majority of these proven breeders were jaguars, pumas, and ocelots.…”
Section: Imbalanced Diets and Fertility In Felids Latin American Catsmentioning
confidence: 99%
“…27 Reproductive Of the 185 male cats assessed, the level of successful captive breeding was low, with only 37 males (20%) classified as proven breeders (produced at least one offspring). 27 The majority of these proven breeders were jaguars, pumas, and ocelots. Reproductive evaluations of these 185 males revealed that 131 males (71%) had sperm in their ejaculates; however, the mean number of sperm/ejaculate for each species was low compared with counterpart values measured in U.S. institutions.…”
Section: Imbalanced Diets and Fertility In Felids Latin American Catsmentioning
confidence: 99%
“…In the last decades, the wild population of ocelots (Leopardus pardalis Linnaeus, 1758) has drastically declined (Murray & Gardner 1997), and one of the ways to conserve the species is keeping genetically viable ex situ populations in facilities such as wild life breeding centers and zoos (Swanson 2003, Cuarón 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos protocolos anestésicos foram propostos para colheita de sêmen em felídeos domésticos e selvagens (Platz Jr & Seager 1978, Howard 1993, Selmi et al 2001, Axnér & Linde-Forsberg 2002, Swanson et al 2003, porém alguns pesquisadores relataram problemas na realização do procedimento. Dificuldades como contaminação por urina, diminuição no volume do ejaculado, ejaculação retrógrada para a bexiga, planos anestésicos inadequados e ineficácia de algumas colheitas estão entre os problemas mais citados (Morais et al 2002, Queiroz 2003, Tebet 2004.…”
Section: Introductionunclassified
“…Em dois dos três animais foi necessária a administração complementar de tiletamina e zolazepam. Swanson et al (2003) relataram utilização da associação de tiletamina e zolazepam (5,0-10,0mg/kg, i.m.) para colheita de sêmen em felídeos neotropicais, informando que tal protocolo produziu plano anestésico adequado para eletroejaculação em todas as espécies, com exceção do puma (Puma concolor) e do gato-mourisco (Puma yagouaroundi).…”
Section: Introductionunclassified